2022
DOI: 10.1021/acs.macromol.2c00545
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis and Self-Assembly of Segmented Hyperbranched Block Copolymers via RAFT-Mediated Dispersion Polymerization Using Segmented Hyperbranched Macro-RAFT Agents

Abstract: Although linear block copolymer assemblies derived from polymerization-induced self-assembly (PISA) have been prepared with a wide variety of structures, examples with hyperbranched block copolymer assemblies have remained elusive. In this work, efficient synthesis and self-assembly of segmented hyperbranched block copolymers (SHBCs) were achieved via reversible addition–fragmentation chain-transfer (RAFT)-mediated dispersion polymerization-induced self-assembly (PISA) using segmented hyperbranched macro-RAFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 87 publications
1
19
0
Order By: Relevance
“…Therefore, from this point, the appearance of a detectable shoulder peak in the SEC trace probably suggests the formation of a highly branched macromolecular structure via the polymerization of vinyl groups of ACP. 34,35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, from this point, the appearance of a detectable shoulder peak in the SEC trace probably suggests the formation of a highly branched macromolecular structure via the polymerization of vinyl groups of ACP. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, from this point, the appearance of a detectable shoulder peak in the SEC trace probably suggests the formation of a highly branched macromolecular structure via the polymerization of vinyl groups of ACP. 34,35 The degree of branching (DB), number-averaged CTA functionality ( f CTA ), and number-averaged segment numbers of POEGMA(m) and P(HSEMA-g-CL) (n) grafts per copolymer are important parameters of a hyperbranched copolymer, which could be calculated as follows:…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%
“…PISA provides a remarkably efficient and versatile platform for the scalable synthesis of block copolymer (BCP) assemblies with the bespoke size and morphology. Despite the most PISA studies being focused on the linear BCPs, the copolymers with the architecture beyond linear BCPs, including miktoarm star copolymers, surface-anchored BCPs, and branched BCPs, have also attracted increasing attentions. For instance, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that the morphologies obtained by PISA are largely dictated by the respective chemical nature and length of solvophilic and solvophobic blocks, 45,46 solids, 47,48 solution conditions [49][50][51] and initiating methods. 52 Compared with the vast majority of research on linear diblock and triblock copolymers, the self-assembling behavior of polymers with more complex architectures under PISA conditions 15,[53][54][55][56][57][58][59] has been much less explored. Zhang et al 60 have reported (P4VP-b-PS) n nanoassemblies with arm number n = 1-4, showing that star-shaped BCPs have more complex morphology than their linear counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the vast majority of research on linear diblock and triblock copolymers, the self-assembling behavior of polymers with more complex architectures under PISA conditions 15,53–59 has been much less explored. Zhang et al 60 have reported (P4VP- b -PS) n nanoassemblies with arm number n = 1–4, showing that star-shaped BCPs have more complex morphology than their linear counterparts.…”
Section: Introductionmentioning
confidence: 99%